Use of Systemic Antibiotics for Acute Otitis Externa: Impact of a Clinical Practice Guideline. Issue 9 (October 2018) - Wang, Xi; Winterstein, Almut G.; Li, Yan; Zhu, Yanmin; Antonelli, Patrick J.
Abstract : Objective: To assess the extent of systemic antibiotic use among patients with acute otitis externa (AOE), as well as the impact of an AOE clinical practice guideline publication in 2006. Study Design: Interrupted time series study of retrospective data. Setting: Medicaid billing data from 29 states between 2002 and 2010. Patients: Patients with age less than 65 years, continuous Medicaid eligibility for 12 months before AOE diagnosis, and dispensation of antibiotics within 1 day before through 3 days after AOE diagnosis. Main Outcome Measures: The proportion of AOE visits that received systemic antibiotics among all AOE visits that were dispensed any antibiotics, systemic or topical. Results: We found 682, 865 AOE visits that received systemic or topical antibiotics for AOE. The proportion of systemic antibiotic therapy either with or without topical therapy was 43.1% before and 38.3% after AOE guideline publication. There was no significant immediate drop (–0.01; 95%CI, –0.031–0.011) or change in trend (0.002; 95%CI, –0.001–0.004) in the prevalence of systemic antibiotic therapy after guideline publication. Conclusion: Publication of an AOE clinical guideline did not lead to a decline in systemic antibiotic therapy as initial AOE treatment. Additional efforts will be needed to curb systemic antibiotic treatment for AOE.